(untitled) (Ciudades, 2017)
This paper studies the relationship between planning and the process of social change in England, during the transition from feudalism to capitalism. As primitive forms of planning, enclosure acts were used to destroy old structures of social reproduction that were hindering the formation of the emergent capitalism in this period. The article describes the communal regime prior to enclosure and the ways of life depending on it. After that, we study the process of passing the laws and how they suppressed that regime. As a corollary, we propose a new historiography of the relationship between planning and social reproduction, which allows a subsequent treatment of the hegemonic and dispossessing instances embedded in our practices.